Photocatalytic activity enhancement of Cu2O cubes functionalized with 2-ethynyl-6-methoxynaphthalene through band structure modulation. Issue 10 (22nd February 2022) - Patra, Anindya Sundar; Kao, Jui-Cheng; Chan, Shang-Ju; Chou, Po-Jung; Chou, Jyh-Pin; Lo, Yu-Chieh; Huang, Michael H.
Abstract : Inert Cu2 O cubes become photocatalytically active with 2E-6-MN functionalization. The molecule-derived bands within the band gap of Cu2 O and charge density distribution over the molecule contribute to the photocatalytic activity appearance. Abstract : Since the exciting discovery that binding of 4-ethynylaniline on inert Cu2 O cubes makes the functionalized cubes highly photocatalytically active toward methyl orange (MO) degradation, binding of 2-ethynyl-6-methoxynaphthalene (2E-6MN) molecules was found to produce a similar effect to activate Cu2 O cubes. A moderate activity enhancement was observed for the functionalized Cu2 O rhombic dodecahedra, while the activity of octahedra only improves slightly. Thus, the degree of photocatalytic activity enhancement is highly facet-dependent. Electron, hole, and radical scavenger tests confirm the photocatalysis results. Electrochemical impedance measurements also show a reduced charge transfer resistance after 2E-6MN modification for cubes and rhombic dodecahedra. Moreover, density functional theory (DFT) calculations have revealed the emergence of narrow bands within the band gaps of Cu2 O100 and 110 surfaces, but not on the 111 surface. Charge density distribution analysis is also insightful to understand the pronounced photocatalytic activity of the modified Cu2 O cubes. Surface functionalization with conjugated molecules represents a new strategy to activate or enhance photoinduced charge transfer of semiconductor materials.